PERSPEKTIF BALANCED SCORE-CARD DALAM PENGUKURAN PRODUKTIVITAS ORGANISASI - Rachmad Hidayat (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
Balanced Scorecard system  may  affect the company’s productivity in the forms of financial perspective, internal business process perspective, and learning as well as growth perspective. A manager shall consider its benefits before implementic the system to the company. This research uses quantitative data obtained from accounting and producting staffs. Data are  analyzd by  using statistical experiment as the analysis tool to test the hypothesi using F test to find out the correlation of research variable simultaneously,  and t-test to find out the relationship of multiple linear regression of equality partialy. And the result is that  there is correlation between company’s productivity and perspectives in Balanced Scorecard. The dominant effect toward the company’s productivity is learning and growth perspective and internal business process perspective.